A região A5 e o controle respiratório durante o desenvolvimento - Taxini, Camila Linhares (2017)
The noradrenergic group A5 is located in the ventrolateral pons and contributes to the maturation of the respiratory system before birth in rats. These neurons are connected to the neural network responsible for respiratory rhythmogenesis. In the present study, we investigated: (1) the influence of the activation of noradrenergic neurons of the A5 region, via purinergic receptors, on the phrenic nerve activity by using in vitro preparations; (2) the participation of A5 noradrenergic neurons in neonates (P7-8 and P14-15) in the control of ventilation during hypoxia and hypercapnia in in vivo experiments by using chemical lesion with anti-dopamine-beta hydroxylase saporin (Anti-DBH-Sap); (3) the involvement of noradrenergic neurons of the A5 region in phrenic and sympathetic nerve activity during the activation of central and peripheral chemoreflex in juvenile rats in in situ preparation using Anti-DBH-Sap into A5 region. Activation of purinergic receptors in noradrenergic neurons of the A5 region by ATP (10 mM) decreased phrenic activity (C4), a reversible effect by applying the purinergic antagonist (Suramin, 10 μM). In vivo and in situ experiments, lesion of the noradrenergic neurons of the A5 region did not promote alteration of resting ventilatory parameters and during hypoxia and hypercapnia, but the sympatho-excitation elicited by either the stimulation of peripheral or central chemoreceptors was attenuated in A5-lesioned rats. Thus, our data suggest that ATP acting in the A5 region reduces respiratory activity after birth, via activation of purinergic receptors. However, from P7, noradrenergic neurons of the A5 region do not participate in the control of ventilation at baseline, or at the central and peripheral chemoreflex. Additionally, the noradrenergic neurons of the A5 region are part of the circuits recruited for the processing of the sympathetic response to the activation of central and peripheral chemoreceptors in unanesthetized juvenile rats.